THE DEVELOPMENT OF NXT-G BASED CHARACTER WRITING ROBOT USING LEGO MINDSTORM NXT - Devi Novayanti, Putu (Universitas Pendidikan Ganesha, 2012)
Robot is one of many technological products which is created to help people in doing their business built of some mechanical and electronic series. There are many types of robot which are made for various necessities. One of them isÂ for educational purpose. One kind of beneficial robot which robot to be developed is writing robot. In Germany, there has been the development of writing robot named NXT 8094 which is able to write characters on an A5 paper only. This study aims at further development of writing robot using combination concepts of mobile robot and arm robot. The research objectives are establishing and implementing the mechanical series of writing robot using Lego Mindstorm NXT, NXT-G based writing robot movement system, Microsoft Visual C# 2005 based writing robot controller system, and measuring the accuracy and the average of time used in writing a character of the writing robot.The software used produce 16 segments of alphabetical and numerical characters. In other hand, the hardware utilized is controlled through a controller software which is used Bluetooth. In operating the robot, the capacity of NXT Brick cell used is between 80-100% in order to obtain maximum result of character writing The use of rechargeable cell is strongly recommended. Besides, the mechanical series using gears have to be adjusted to reduce friction which potentially slows the device. The accuracy percentage of the characters writing is measured by using descriptive statistical and mean formula to gain theÂ average of time in writing. The software used in this study is built by using Microsoft Visual C# 2005. This software is also implemented and tried-out in the Windows XP operating system.Â THE DEVELOPMENT OF NXT-G BASED CHARACTER WRITING ROBOT USING LEGO MINDSTORM NXT